Sliding Dynamic Behavior of a Nanobubble on a Surface - Wu, Cyuan-Jhang; Chu, Kang-Ching; Sheng, Yu-Jane; Tsao, Heng-Kwong (Journal of physical chemistry. C, 2017)
The sliding dynamics of a nanobubble adhered to surfaces is an intriguing and yet to be fully understood aspect. In this work, the dynamics of stable surface nanobubbles in a fluid subject to body force is explored by many-body dissipative particle dynamics simulations at low Reynold numbers Re ∼ O(0.1). It is found that in addition to surface roughness, the nanobubble motion depends significantly on the bubble shape which relates to the bubble angle (θb) associated with surface wettability. The mobility grows substantially with decreasing θb and the surface nanobubble can rise faster than a freely rising nanobubble. Moreover, owing to the decrease of both the frontal area and drag coefficient, the mobility of a flat bubble on a smooth surface can be many times greater than that of a spherical bubble. The influence of surface roughness depends on the surface wettability. The sliding motion is impeded by surface roughness because of capillary pinning. However, it is interesting to find that for θb less than a certain small value, the mobility on the rough surface can surpass that on the smooth one due to the superlyophobicity reducing the friction resistance. This extraordinarily rapid motion of surface nanobubbles may possess some potential applications for clean technologies.